Synthesis, Molecular Docking Analysis and in Vitro Biological Evaluation of Some New Heterocyclic Scaffolds-Based Indole Moiety as Possible Antimicrobial Agents - Hassan, Entesar A.; Shehadi, Ihsan A.; Elmaghraby, Awatef M.; Mostafa, Hadir M.; Zayed, Salem E.; Abdelmonsef, Aboubakr H. (Frontiers in Molecular Biosciences, 2022)
In the present study, a general approach for the synthesis of 1-(1H-indol-3-yl)-3,3-dimercaptoprop-2-en-1-one (1) and 5-(1H-indol-3-yl)-3H-1,2-dithiole-3-thione (2) was performed. They are currently used as efficient precursors for the synthesis of some new compounds bearing five- and/or six-membered heterocyclic moieties, e.g. chromenol (3, 4), 3,4-dihydroquinoline (7, 8) and thiopyran (10, 12)-based indole core. In addition, molecular docking studies were achieved and showed that all the newly synthesized compounds are interacting with the active site region of the target enzymes the targets UDP-N-acetylmuramatel-alanine ligase (MurC), and human lanosterol14α-demethylase, through hydrogen bonds and pi-stacked interactions. Among these docked ligand molecules, the compound (9) was found to be with the minimum binding energy (-11.5 and -8.5 Kcal/moL) as compared to the standard drug ampicillin (-8.0 and -8.1 Kcal/moL) against the target enzymes UDP-N-acetylmuramatel-alanine ligase (MurC), and Human lanosterol14α-demethylase, respectively. Subsequently, all new synthesized analogues were screened for their antibacterial activities against Gram-positive (Bacillus subtilis), and Gram-negative bacteria (Escherichia coli), as well as for antifungal activities against Candida albicans and Aspergillus flavus. The obtained data suggest that the compounds exhibited good to excellent activity against bacterial and fungi strains. The compound (E)-2-(6-(1H-indole-3-carbonyl)-5-thioxotetrahydrothieno[3,2-b]furan-2(3H)-ylidene)-3-(1H-indol-3-yl)-3-oxopropanedithioic acid (9) showed the high binding affinity as well as an excellent biological activity. Therefore, it could serve as the lead for further optimization and to arrive at potential antimicrobial agent.